Characteristics of patients with neurotic disorders requiring long‐term treatment: Relationship to “nervous personality” as described in Morita's Shinkeishitsu theory - Hiroshi Matsumoto; Takashi Uchino; Tomoyuki Funatogawa; Masafumi Mizuno; Takahiro Nemoto (PCN Reports)
Abstract Aim Few studies have investigated the association between premorbid personality and the prognosis of neurotic disorders. The aim of this study was to investigate the relationship between the presence of a “nervous personality” described in Morita's Shinkeishitsu theory and the duration of treatment in patients with neurotic disorders. Methods The study included 70 patients aged ≥15 years old who first visited the Department of Psychiatry, Toho University Omori Medical Center, between January 2010 and December 2010 and were diagnosed as having neurotic disorders. The subjects' medical records over a 10‐year period from 2010 until 2020 were examined retrospectively to determine the influence of the presence of a “nervous personality” in the subjects on the duration of their treatment. Results There were no significant differences in the basic demographic characteristics or severity of illness at the first visit between groups with and without a “nervous personality.” The mean and median duration of treatment were 25 months and 5 months in the group with a “nervous personality,” and 5 months and 2 months in the group without a “nervous personality,” respectively. Kaplan–Meier analysis revealed a significant difference in the duration of treatment between the two groups. Multiple regression analysis performed using treatment duration as the dependent variable identified only presence of a “nervous personality” among the independent variables as a significant factor influencing the duration of treatment, with the duration of treatment being 20 months longer in the group of subjects with a “nervous personality.” Conclusion The presence of a “nervous personality,” as described in Morita's Shinkeishitsu theory, may prolong the required duration of treatment in patients with neurotic disorders.